Unqualified Audit Opinions and Their Role in Promoting Transparent, Accountable, and Just Governance Reform - Amiq, Bachrul; Hamdani, Fathul; Prawesthi, Wahyu; Aribawa, Muhammad Yustino; Begishev, Ildar (Magister of Law, Faculty of Law, University of Mataram, 2025)
This study examines the effect of the Supreme Audit Agency (BPK) audit results with an unqualified opinion (WTP) on efforts to improve clean governance in Indonesia. The WTP opinion shows that the financial statements of government entities have been prepared by applicable accounting standards and regulations. Using a normative legal research approach, this study examines the relevance of the WTP opinion as the main indicator of transparency, accountability, and integrity in state financial management. The results show that the WTP opinion has a positive impact in increasing transparency and accountability, strengthening supervision and efficiency of financial management, reducing the potential for corruption, and building public trust in the government. In addition, the WTP opinion also encourages bureaucratic reform through technology adoption, strengthening human resources, and more effective budget planning. This research emphasizes the importance of WTP opinion as a strategic tool in realizing good and sustainable governance.